Pseudomonas aeruginosa lasI/rhlI quorum sensing genes promote phagocytosis and aquaporin 9 redistribution to the leading and trailing regions in macrophages - Holm, Angelika; Karlsson, Thommie; Vikström, Elena (Frontiers in Microbiology, 2015)
Pseudomonas aeruginosa controls production of its virulence factors and biofilm development via the quorum sensing (QS) system. QS signals also interact with and affect the behavior of eukaryotic cells. Host water homeostasis and aquaporins (AQP) are essential during pathological conditions since they interfere with the cell cytoskeleton and signaling, and hereby affect cell morphology and functions. We investigated the contribution of P. aeruginosa QS genes lasI/rhlI to phagocytosis, cell morphology, AQP9 expression and distribution in human macrophages, using immunoblotting, confocal and nanoscale imaging. Wild type P. aeruginosa with a functional QS system was a more attractive prey for macrophages than the lasI/rhlI mutant lacking the production of QS molecules 3O-C12-HSL and C4-HSL, and associated virulence factors. The P. aeruginosa infections resulted in elevated AQP9 expression and relocalization to the leading and trailing regions in macrophages, increased cell area and length; bacteria with a functional QS system lasI/rhlI achieved stronger responses. We present evidence for a new role of water fluxes via AQP9 during bacteria–macrophage interaction and for the QS system as an important stimulus in this process. These novel events in the interplay between P. aeruginosa and macrophages may influence on the outcome of infection, inflammation and development of disease.